2003
DOI: 10.1177/0148607103027004277
|View full text |Cite
|
Sign up to set email alerts
|

Gastric electrical stimulation for gastroparesis improves nutritional parameters at short, intermediate, and long‐term follow‐up

Abstract: Gastric electrical stimulation implantation resulted in improvement of nutritional parameters throughout the first 12 months, as nausea and vomiting decreased and oral intake increased. This improvement in nutritional measures is maintained long-term and is associated with improvements in quality of life. Gastric electrical stimulation should be considered as a therapeutic option for any patients with refractory GP and nutritional compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 7 publications
2
86
0
3
Order By: Relevance
“…Results of other studies suggest favorable responses, if they are to occur, will take place within the initial 3-6 months, although this needs further study. In an abstract with long-term patient follow-up, investigators observed 26% and 44% reductions in nausea and vomiting, respectively, persisting for up to 10 years [11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results of other studies suggest favorable responses, if they are to occur, will take place within the initial 3-6 months, although this needs further study. In an abstract with long-term patient follow-up, investigators observed 26% and 44% reductions in nausea and vomiting, respectively, persisting for up to 10 years [11].…”
Section: Discussionmentioning
confidence: 97%
“…There have been other studies reporting on an individual institution's experience with Enterra GES [4][5][6][10][11][12]. In two single center studies, electrical stimulation has been reported to improve nutritional status, limit the need for prokinetic and antiemetic medications, and reduce the need for hospitalizations and supplemental nutrition [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Near-completion gastrectomy (NCG) has proved useful in small series of patients [21] , but data on longterm follow-up has been lacking. Gastric electrical stimulation can be of value in the management of gastroparesis [22][23][24] , in which the patients with PGS received continuous highfrequency/low-energy gastric electrical stimulation via electrodes deposited in the muscular wall of the antrum and connected to a neurostimulator in an abdominal wall pocket. This method produced entrainment of the intrinsic slow wave and promoted contractions in phase III with the normal slow wave.…”
Section: Discussionmentioning
confidence: 99%
“…In one uncontrolled multicenter trial, 35 of 38 patients experienced > 80% reductions in nausea and vomiting which persisted for 2.9-15.6 mo, with an associated 5.5% increase in weight and reduced requirement of supplemental nutrition [123] . Other studies reported similar long-term symptom benefits, which may persist for at least 10 years with improvements in body mass index, serum albumin and glycemic control [124,125] . In the only controlled trial of GES, 33 patients with idiopathic or diabetic gastroparesis completed a 2-mo double-blind, crossover, sham stimulation-controlled phase followed by 12 mo uncontrolled observation, with the device activated [119] .…”
Section: Gesmentioning
confidence: 72%